Situation of Gender Based Violence against Women and girls in Nepal - Dhakal, Radha Devi (DMC Research Journal, 2018)
Various forms of violence against women and girls were found to be prevalent throughout the life-cycle of women as a global phenomenon. Worldwide one third women experience physical or sexual abuse in their lifetime. The terms gender based violence and violence against women are used interchangeably. Women and girls are experiencing violence in their lifetime regardless of their age, religion, caste, marital status and pregnancy as well. They are facing violence at home, work place, public transport, public places.